Development, simulation, and validation of sliding self-centering steel brace with NiTi SMA wires. (1st April 2022) - Sun, Guohua; Liu, Han; Liu, Wenyuan; Yang, Wenxia
Highlights: An innovative sliding-type self-centering steel brace with NiTi SMA wires was proposed. Five sliding-type self-centering steel brace specimens were tested under cyclic loading. Sliding-type feature, self-centering behavior, and energy dissipation capacity were addressed. The restoring force model of self-centering steel brace was presented. Abstract: This study proposes an innovative sliding self-centering (SC) brace to reduce or eliminate residual deformation after strong earthquakes. The brace uses tension-only nickel and titanium (NiTi) shape-memory alloy wires to generate SC behavior and tension-only steel bars to provide energy dissipation, axial strength, and axial stiffness. The proposed sliding SC brace concept and details are outlined, and tests are conducted on variations of the proposed brace subject to cyclic loading to investigate their hysteretic behavior. The experimental results demonstrated that the proposed brace exhibited a double-flag-shaped hysteretic response, controlled axial strength, and preferable SC behavior. An important advantage is that the tension-only steel bars of the proposed brace exhibit a sliding hysteretic response, which can significantly reduce the number of NiTi shape-memory alloy wires and decrease the cost of the brace. The proposed sliding SC brace mechanisms and governing equations for practical engineering designs are presented. A cyclic restoring force model with a trilinear skeleton curve, which reflected the sliding characteristics and SC features, was proposed and calibrated using experimental results. Additionally, the finite element analysis results were aligned with the test results. Three main design parameters affecting the sliding SC brace energy dissipation and SC ability are addressed.